Sharing control [multiple miniature robots]. - Rybski, P.E.
Presents a framework for the operation and coordination of multiple miniature robots. Simple teleoperation can be useful in many situations, but the operator's attention must be completely dedicated to controlling the robot. This may be difficult when the task requires the use of multiple robots. This article introduces a layered system that has been developed to facilitate multimodal control. This system includes user interfaces (UI) for teleoperation clients and robust sensor interpretation algorithms for autonomous control clients. A distributed software control architecture dynamically coordinates hardware resources and shares them between the various clients, allowing for simultaneous control of multiple robots.
Keywords: UI; Distributed software control architecture; Multilayered system; Multimodal control; Multiple miniature robot coordination; Robust sensor interpretation algorithms; Teleoperation; Telerobotics; User interfaces